ANALISIS EVALUASI DAN PENJAMIN MUTU PENDIDIKAN DIGITAL - Irwandi; Irwan B; Heru Sandi Susilo; Andi Warisno; Nila Wati Tajuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information and communication technology has driven the transformation of education toward digital learning. Digital education offers various advantages, including flexibility in learning time and place, wider access to educational resources, and enhanced interaction through digital platforms. However, the implementation of digital education also presents challenges related to service quality, learning effectiveness, human resource readiness, and technological infrastructure. Therefore, evaluation and quality assurance play a crucial role in ensuring that digital education is implemented in accordance with established standards. Evaluation in digital education is conducted to measure the effectiveness of learning processes, the achievement of educational objectives, and the satisfaction of learners and stakeholders. Meanwhile, quality assurance in digital education refers to a systematic process aimed at maintaining and continuously improving educational quality through planning, implementation, monitoring, evaluation, and continuous improvement. Effective evaluation and quality assurance enable educational institutions to enhance the quality of digital learning services, optimize the use of technology, and produce graduates who are competent and well-prepared to face the challenges of the digital era.